Accuracy analysis of optical-based measurements considering distance, height, and temperature variations - Eren, Mehmet (SCIENTIFIC SCHOLAR LLC, 2026)
Refraction is one of the most important factors affecting the accuracy of optical and electromagnetic measurement systems. In this study, the effect of refraction on measurement accuracy was investigated by processing video camera images obtained under different distances, temperatures, and object height conditions. Video camera recordings directed at a fixed target were processed using the Template Matching method in MATLAB. The normalized cross correlation (NCC) algorithm was used to prevent the effects of brightness or contrast differences and to ensure a more reliable comparison. A time series of target position changes (caused by refraction) was obtained, and the results were interpreted using statistical measures such as standard deviation (6) and the F-test. The findings showed that the 6 increased as distance and temperature increased, while the deviation decreased as the target height increased. Furthermore, the deviations of the horizontal component were found to be higher than those of the vertical component. For the first measurement, the deviations varied between +/- 0.3 and +/- 4.50 mm, depending on temperature and distance. In the second measurement, the deviation increased to +/- 6.8 mm when the measured object was 0.50 m above the ground, but decreased to +/- 2.6 mm at a height of 2.50 m. The deviation values obtained in the current study are not a problem for applications where a few centimeters of precision are sufficient in rough construction work. However, in applications requiring high precision, such as industrial measurements and deformation monitoring, refraction effects must be considered. The pressure factor was not investigated in this study, and future studies are recommended to evaluate the contribution of each parameter to refraction separately.
Keywords: Image processing; Optical measurements; Refraction; Temperature effect; Template matching; CALIBRATION; VISION; Science & Technology - Other Topics